Innovative Empowerment Strategies for Conical Hat (Caping) Craftsmen in Biraeng Village, Minasatene District, Pangkep Regency, South Sulawesi - Sumandiyar, Adi (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
This research aims to obtain in-depth information about the quality of Conical Hat production (Caping) of the women's group of Conical Hat craftsmen is still low compared to the same production in the market, and the market share of Conical Hat handicrafts of the women's group is still limited to the local market. The type of research is descriptive qualitative with data analysis conducted in four stages; data collection, data reduction, data presentation, and conclusion drawing. This research is also supported by data triangulation. The results showed that in improving the quality of production of Conical Hat (Caping), the group of housewives of Conical Hat craftsmen is still low compared to the same production in the market, so training and mentoring of Conical Hat craftsmen groups are needed to optimize production quality, to attract interest from consumers. Furthermore, the market share of Conical Hat crafted by women's groups is still limited to the local market by conducting techniques and assistance in marketing handicraft products.